Cautious Curiosity: A Novel Approach to a Human-Like Gameplay Agent - Zhou, Chujin; Machado, Tiago; Harteveld, Casper (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2023)
We introduce a new reward function direction for intrinsically motivated reinforcement learning to mimic human behavior in the context of computer games. Similar to previous research, we focus on so-called ``curiosity agents'', which are agents whose intrinsic reward is based on the concept of curiosity. We designed our novel intrinsic reward, which we call ``Cautious Curiosity'' (CC) based on (1) a theory that proposes curiosity as a psychological definition called information gap, and (2) a recent study showing that the relationship between curiosity and information gap is an inverted U-curve. In this work, we compared our agent using the classic game Super Mario Bros. with (1) a random agent, (2) an agent based on the Asynchronous Advantage Actor Critic algorithm (A3C), (3) an agent based on the Intrinsic Curiosity Module (ICM), and (4) an average human player. We also asked participants (n = 100) to watch videos of these agents and rate how human-like they are. The main contribution of this work is that we present a reward function that, as perceived by humans, induces an agent to play a computer game similarly to a human, while maintaining its competitiveness and being more believable compared to other agents.